Spontaneous bleeding of an arachnoid cyst: a rare cause of thunderclap headache - Domingues, Renan; Ribeiro, Saulo Ramos; Mello, Ana Lucia de Carvalho; Miranda, Carolina Franciely Vitor; Pacheco, Evelyn de Paula; Carvalho, Joao José Freitas de (Headache Medicine, 2022)
Introduction A thunderclap headache is a severe headache that starts suddenly and may be a sign of a condition that can be life threatening. Objective To present a case of a rare cause of thunderclap headache. Case presentation A 37-year-old female patient was admitted in the neurological emergence service of a private hospital in the city of São Paulo. She had sudden, explosive, and pulsatile headache, with photophobia and phonophobia. The neurological examination had no focal signs. She had deep vein thrombosis in 2014 in the past and since then she has been irregularly using Warfarin. She underwent CT and MRI of the skull that showed enlargement of the bilateral retrovermian and retrocerebellar cerebrospinal fluid space, with thin membranes/septations inside, and heterogeneous content, with deposition of hemoglobin degradation products. Such findings are consistent with a retrovermian arachnoid cyst with hemorrhagic content. The INR was 1. Conservative and symptomatic treatment was started, and control CT was performed on the second day of hospitalization, demonstrating almost complete reabsorption of hematic material. The patient was discharged after 2 days of hospitalization with complete headache improvement. Conclusion Arachnoid cysts are collections of fluid located between the meningeal membranes. They are congenital and are formed due to a valve defect in the arachnoid membranes leading to a collection of cerebrospinal fluid (CSF) in its interior. Most arachnoid cysts are an incidental finding. About 1 to 2% of the population has an arachnoid cyst and symptoms appear when the cyst increases in size or bleeds. Our patient had a are complication of and arachnoid cyst not related with the use of anticoagulant. Keywords: Thunderclap headache, Arachnoid Cyst Bleeding, Arachnoid Cyst.